Pembuatan Biodiesel Dari Cpo Off Grade Menggunakan Reaktor Membran (Variasi Katalis Dan Fraksi Mol Umpan - Enang Vovilya; Syarfi Syarfi; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Membrane reactor is an alternative technology that is used in the manufacture of biodiesel, one of the advantages that the reaction and separation process takes place in a single stage simultaneous. This research aims to study the effect of the variation of the catalyst and mole ratio feed CPO off grade - methanol in biodiesel production, a pretreatment process performed on the raw materials that aim to reduce the FFA content CPO off grade, the results obtained pretreatment FFA content of 0.79%, then performed transesterification process which was held in a membrane reactor with a variation of the mole ratio of CPO off grade -methanol 1:12, 1:18, and 1:24, the concentration of the base catalyst 1% -wt, 1.5% -wt and 2% -wt, pressure transmembrane 2 bar and a temperature of 60 oC process. The results showed biodiesel production using membrane reactor reached 72.02% yield on the condition of the mole ratio of 1:18 with a concentration of 2 %-wt, characteristics of biodiesel produced meets the quality standards of biodiesel in Indonesia including biodiesel, densityis 860-884 kg/m3, viscosity of biodiesel is 5.14 to 5.76 mm2/s, Flash Point is 158-161 °C, Acid Numberis 0.62 to 0.75 mg-KOH/g.Keywords: biodiesel, CPO off grade, membrane reactor, mol ratio, catalyst concentration.